ANALISIS PENGENDALIAN KUALITAS CRUDE PALM OIL: STUDI KASUS INDUSTRI PENGOLAHAN KELAPA SAWIT JAMBI - Anjasmi, Arie Yuniken; Zulhamidi, Zulhamidi (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2021)
One of the industries involved in palm oil processing. PKS in Jambi process fresh fruit bunches (FFB) and do not always produce crude palm oil (CPO) according to the standards set by the company. The CPO produced by the company is damaged due to various factors. So SPC will be used as a tool in analyzing CPO quality control in one of the PKS industries in Jambi. The causes of high free fatty acids are many factors, including poor fruit acceptance due to defects, less strict fruit sorting. Weather factors that cause fruit to take a long time in the garden or unloading field. Slippery roads cause fruit to get stuck on the road for days. The proposal to improve the quality of CPO is to implement quality control starting from the arrival of raw materials, until the final process of TBS processing which is the distribution process of CPO in storage tanks. The main improvement that the company needs to do is to focus on the factors that cause the problem of quality decline, namely the raw material factor, the machine factor and the human factor that processes CPO.